If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 1) = 3(2x + -7) Reorder the terms: 2(1 + 3x) = 3(2x + -7) (1 * 2 + 3x * 2) = 3(2x + -7) (2 + 6x) = 3(2x + -7) Reorder the terms: 2 + 6x = 3(-7 + 2x) 2 + 6x = (-7 * 3 + 2x * 3) 2 + 6x = (-21 + 6x) Add '-6x' to each side of the equation. 2 + 6x + -6x = -21 + 6x + -6x Combine like terms: 6x + -6x = 0 2 + 0 = -21 + 6x + -6x 2 = -21 + 6x + -6x Combine like terms: 6x + -6x = 0 2 = -21 + 0 2 = -21 Solving 2 = -21 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 15j-11j=20 | | -x^3+4x^2-5x+2=0 | | (3x+5)+(x+2)=4(x-1)+10 | | t-84=72 | | x^2-16x+22=0 | | 121x^2+22x+x=0 | | (3v^4+8)-(8-v^4)= | | x+55=10 | | -5u+35=3(u-9) | | 2n(2-4)= | | 5+m=-6 | | 8x+5=3x+5 | | 3=b+6+2b | | 4.1x+1.1=8.3-x | | x-(x-3)+2=7(2x+4)-19 | | 15+7timesx=99 | | 4x^2-24x=8 | | 8y-2y-3=3 | | 5(2x+4)=12x+28 | | x=3[-2x+9]+8 | | 5(1+5n)=-95 | | 3(x+8)=2(4x+17) | | 2z+-3=-2.68 | | 121x^2+22x=0 | | x^2+3x-2=ab | | -x^2+1x-20=0 | | 3(3m+4)=-24 | | 3(6-x)+7x=x-7 | | 2(6x+4)=7x | | 22x-5.2x+4=0 | | X=x-12 | | 4m(m+2)= |